2014
DOI: 10.5430/cns.v2n2p16
|View full text |Cite
|
Sign up to set email alerts
|

Operating room nurse manager competencies in Greek hospitals

Abstract: Aim: The purpose of this study was to identify and measure managerial competencies, skills and knowledge necessary for a competent Operating Room (OR) nurse manager so to provide quality care. Methods:The Nurse Manager Questionnaire was used in General and Army Hospitals with at least 5 operating suites. 153 Operating Room nurses and Operating Room nurse managers rated the 53 skills of the Questionnaire depending on how essential those skills are for OR nurse manager (RR=81%). The 53 skills were separated in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
29
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 10 publications
5
29
2
Order By: Relevance
“…Analysis revealed that nurse managers often had a bachelor's degree (Karathanasi et al, ; Martin & Waring, ; Rudolfsson & Flensner, ; Rudolfsson et al, ) and few were academically qualified (Kondrat, ; Rudolfsson & Flensner, ; Rudolfsson et al, ). In one study (Siirala et al, ), there was no mention of educational degrees for nurse managers.…”
Section: Key Issuementioning
confidence: 99%
See 4 more Smart Citations
“…Analysis revealed that nurse managers often had a bachelor's degree (Karathanasi et al, ; Martin & Waring, ; Rudolfsson & Flensner, ; Rudolfsson et al, ) and few were academically qualified (Kondrat, ; Rudolfsson & Flensner, ; Rudolfsson et al, ). In one study (Siirala et al, ), there was no mention of educational degrees for nurse managers.…”
Section: Key Issuementioning
confidence: 99%
“…The nurse manager's clinical experience was assessed in three studies (Martin & Waring, ; Rudolfsson & Flensner, ; Schroeder & Worral‐Carter, ), and three studies assessed managerial experience (Karathanasi et al, ; Rudolfsson et al, ; Schroeder & Worral‐Carter, ). Only Martin and Waring's () study focused on nurse manager's professional background in a management position.…”
Section: Key Issuementioning
confidence: 99%
See 3 more Smart Citations